Manejo de cobertura de solo na produção de brócolis - Kremer, Jhonatan Indicatti (My University, 2025)
The broccoli crop has important nutritional values for the human body and health. The objective of this work is to test different types of ground cover in the production of broccoli, as alternatives to producers, as this technique is not commonly used in the crop. The management of soil cover, either with the use of Mulching plastic, or with black oat straw, or other coverings, improves the cultivation environment, providing physical and chemical improvements in soil characteristics, such as reducing erosion, maintaining temperature and moisture, reducing the loss of fertilizers and correctives by leaching, in addition to acting as a physical barrier against weeds. The experiment was carried out on the property of Hortigranjeiros Guido Kremer, in Caxias do Sul/RS, using broccoli from the cultivar Legacy. The evaluated treatments were: a) planting on white Mulching plastic; b) planting on black oat straw (Avena strigosa Schieb) and c) planting on bare soil. A randomized block design with 3 treatments and 8 replications was used, and each plot consisted of 133 plants, with 10 plants being randomly chosen for evaluations. The parameters evaluated were: stalk size; size and weight of heads and sanity. The data obtained were subjected to analysis of variance and means compared by Tukey test at 5% probability. According to the results obtained, it was concluded that the cultivation of broccoli on Mulching plastic showed better vegetative development of plants in relation to stem, head size and head weight. [resumo fornecido pelo autor]
A cultura dos brócolis possui importantes valores nutricionais para o organismo e saúde humana. O objetivo do presente trabalho é testar diferentes tipos de cobertura de solo na produção de brócolis, como alternativas aos produtores, pois não é comum a utilização desta técnica na cultura. O manejo de cobertura de solo, seja com a utilização de plástico Mulching, seja com palhada de aveia preta, ou outras coberturas, melhora o ambiente de cultivo, proporcionando melhorias físicas e químicas nas características do solo, como diminuição da erosão, manutenção da temperatura e umidade, redução da perda de adubos e corretivos por lixiviação, além de agir como uma barreira física contra as plantas daninhas. O experimento foi realizado na propriedade de Hortigranjeiros Guido Kremer, em Caxias do Sul/RS, utilizando-se brócolis da cultivar Legacy. Os tratamentos avaliados foram: a) plantio sobre plástico Mulching branco; b) plantio sobre palhada de aveia preta (Avena strigosa Schieb) e c) plantio sobre solo desnudo. Utilizou-se delineamento em blocos casualizados com 3 tratamentos e 8 repetições e cada parcela constituída de 133 plantas, sendo escolhidas, ao acaso, 10 plantas para avaliações. Os parâmetros avaliados foram: tamanho de talo; tamanho e peso das cabeças e sanidade. Os dados obtidos foram submetidos à análise de variância e as médias comparadas pelo teste Tukey a 5% de probabilidade. De acordo com os resultados obtidos, concluiu-se que o cultivo de brócolis sobre plástico Mulching apresentou melhor desenvolvimento vegetativo das plantas com relação ao talo, ao tamanho da cabeça e ao peso da cabeça. [resumo fornecido pelo autor]
Keywords: Agronomia; Brócolo - Cultivo; Palha - Agricultura